Faktor Yang Mempengaruhi Tax Avoidance Pada Perusahaan Barang Konsumsi Yang Terdaftar Di BEI - Mariani, Desy (Institut Bisnis dan Informatika Kesatuan, 2020)
This research is conducted to analyze the influence of liquidity, leverage, sales growth and capital intensity of tax avoidance. The population in this research is used secondary data from the financial statement of sub sector good consumer companies listed in the Indonesia Stock Exchange in 2014 – 2018 as many as 48 companies. This research used purposive sampling method and obtained 24 companies for sample. The data analysis used double linear regression analysis with program SPSS version 20. The result of this research show that sales growth have positive effect on tax avoidance. While liquidity,leverage and capital intensity have not effect on tax avoidance.